Amorphous solid electrolyte and preparation method thereof
The use of Li2CO3 and LiI in a ball milling process forms a stable, non-flammable amorphous solid electrolyte, addressing the instability and cost issues of sulfide electrolytes and improving battery safety and efficiency.
Patent Information
- Application Number
- CN202411443435.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-24
AI Technical Summary
Amorphous sulfide solid electrolytes are unstable to water and oxygen, leading to high costs due to the use of expensive Li2S, while amorphous halide solid electrolytes are prone to reduction and require additional buffer layers, compromising battery safety and efficiency.
A preparation method using Li2CO3 and LiI as raw materials, avoiding S and Li2S, with a ball milling process to form an amorphous solid electrolyte xLi2CO3-yLiI, which includes X-ray diffraction testing to ensure amorphous structure and separation of ball milling balls, resulting in a non-flammable electrolyte with high ionic conductivity.
The method produces an amorphous solid electrolyte with improved stability, safety, and reduced costs, enhancing battery performance and scalability by using inexpensive materials and optimizing ionic conductivity through configurational entropy and isotropic migration.
Smart Images

Figure CN119181848A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of all-solid-state batteries, and in particular to an amorphous solid electrolyte and a preparation method thereof. Background Art
[0002] Amorphous sulfide and amorphous halide solid electrolytes have small bulk modulus, easy compaction, high conductivity, wide composition variation, and are non-flammable. All-solid-state batteries using them have attracted increasing interest from researchers due to their potential high rate, high safety, and high specific energy characteristics.
[0003] A typical example of an amorphous sulfide solid electrolyte is a binary system based on the framework of Li2S-P2S5, which can be a mixture of several glass phases and microcrystals, including microcrystalline phases such as Li3(PS4), Li4(P2S7) and Li2(P2S6) and the so-called thio-LISICON II. The preparation method is to perform high-energy ball milling on Li2S, P2S5, SiS2, B2S3, etc. to form a uniform amorphous product. When the S in the system is 2- When anion doping is performed, such as O 2- 、Se 2- ,I - The appropriate amount of Li can be introduced + Vacancy or interstitial Li + , change the short-term or long-term Li + The transmission path and potential barrier, increase or decrease the lattice energy of the crystal, and strengthen the ionic bond, thereby changing the ion transport properties and lattice rigidity of the ion conductor. As reported in the non-patent document Sulfide Solid Electrolytes for Lithium Battery Applications, the general ionic conductivity of amorphous sulfide solid electrolytes is between 0.1 and 1 mS / cm.
[0004] Amorphous sulfide solid electrolytes are relatively stable to metallic lithium at low potentials. However, one of the necessary materials used is Li2S. Li2S is expensive and unstable to water and oxygen. After being oxidized or reacting with water, the product cannot be restored by simple baking; the gaseous reaction products H2S and SO2 are harmful to humans.
[0005] Amorphous halide solid electrolytes cannot directly contact the negative terminal because the central cation is often a high-valent heavy metal ion with high electron affinity and low Fermi level. It is easy for metallic lithium or electrons to be transferred to its valence electron orbit at low potential. Otherwise, it will be reduced, causing the electrolyte structure to be destroyed and the battery to short-circuit.
[0006] In order to solve the expensive problem of Li2S, non-patent literature A Cost-Effective Sulfide Solid Electrolyte Li7P3S 7.5 O 3.5 A new structure of amorphous sulfide electrolyte Li7P3S with Low Density and Excellent Anode Compatibility was proposed 7.5 O 3.5 , its room temperature ionic conductivity is about 0.56mS / cm. The synthesis of this material uses LiOH and P2S5 as raw materials, and does not require expensive Li2S, so the raw material cost is only US$14.42 / kg. Unlike most solid electrolytes, it is below the commercialization threshold of US$50 / kg.
[0007] In order to solve the problem that amorphous halide solid electrolytes are easily reduced, the current effective improvement method is not to improve the amorphous halide solid electrolytes, but to add a modification layer. For example, the non-patent document New Oxyhalide Solid Electrolytes with High Lithium Ionic Conductivity>10mScm -1 For All-Solid-State Batteries, Li6PS5Cl is used as a buffer layer to solve the lithium problem. Li-In alloy is also used as the negative electrode to increase the potential of the negative electrode. The same method is also reported in patents CN113015694B and CN116741935A.
[0008] From the above content, it is not difficult to find that the problem with amorphous sulfides is that although there are means to solve the expensive problem of Li2S, it is still impossible to solve the instability of the final synthesized electrolyte material to water and oxygen caused by P2S5 as a component; amorphous halide solid electrolytes need to rely on lithium-stable sulfide solid electrolytes as a buffer layer, introducing the shortcomings of sulfides into the battery system. Summary of the invention
[0009] The present application provides an amorphous solid electrolyte and a preparation method thereof, which uses a primary lithium salt product Li2CO3 as one of the raw materials, does not contain S that is unstable to water and oxygen 2- ions, avoiding the problem of sulfide electrolyte materials being unstable to lithium negative electrodes. In addition, the preparation raw materials are inexpensive and the preparation method is simple, which is conducive to large-scale production.
[0010] In one aspect, the present application provides a method for preparing an amorphous solid electrolyte, the method comprising:
[0011] Li2CO3 and LiI are weighed in a molar ratio of x:y to obtain a raw material; wherein x+y=1,0 <x<1,0<y<1;
[0012] The prepared raw materials and ball milling balls are placed in a ball milling jar for ball milling to obtain the amorphous solid electrolyte xLi2CO3-yLiI; wherein the ball milling time corresponding to the ball milling treatment is 1-50h, and the ball milling speed is 200-500rpm; the amorphous solid electrolyte xLi2CO3-yLiI is formed by stacking a plurality of spherical amorphous solid electrolyte particles, and the particle size range of the amorphous solid electrolyte particles is 0.5-5μm.
[0013] Furthermore, the preparation raw materials and ball milling balls are placed in a ball milling jar for ball milling to obtain the amorphous solid electrolyte xLi2CO3-yLiI, comprising:
[0014] Placing the raw material and the ball milling balls in the ball milling jar for ball milling to obtain a mixture of the ball milling balls and the initial product; the mass ratio of the raw material to the ball milling balls is 1:(1-50);
[0015] Performing an X-ray diffraction test on the initial product to obtain a test result of the initial product;
[0016] If the test result of the initial product indicates that the initial product has no characteristic peak within the range of 2θ=20-30°, it is determined that the initial product is the amorphous solid electrolyte xLi2CO3-yLiI.
[0017] Furthermore, the method further comprises:
[0018] If the test result of the initial product indicates that the initial product has the characteristic peak in the range of 2θ=20-30°, the ball milling treatment is continued until the product of the ball milling treatment has no characteristic peak in the range of 2θ=20°-30°, and the product of the ball milling treatment is determined to be the amorphous solid electrolyte xLi2CO3-yLiI.
[0019] Further, if the test result of the initial product indicates that the initial product has no characteristic peak in the range of 2θ=20-30°, then after determining that the initial product is the amorphous solid electrolyte xLi2CO3-yLiI, the method comprises:
[0020] Transferring the mixture of the ball milling balls and the amorphous solid electrolyte from the ball milling jar to a screen;
[0021] The mixture of the ball-milling balls and the amorphous solid electrolyte is separated through the sieve to obtain the amorphous solid electrolyte; the aperture of the sieve is smaller than the diameter of the ball-milling balls.
[0022] Further, the ignition point of the amorphous solid electrolyte xLi2CO3 - yLiI is greater than 1000 °C.
[0023] Further, the ionic conductivity of the amorphous solid electrolyte xLi2CO3 - yLiI is 4.9×10 -4 -8.8×10 -2 mS / cm.
[0024] Further, the amorphous solid electrolyte particles include amorphous solid electrolyte particles with a first particle size and amorphous solid electrolyte particles with a second particle size; wherein, the first particle size ranges from 2.1 - 5 μm, and the second particle size ranges from 0.2 - 2 μm.
[0025] Further, the number of the amorphous solid electrolyte particles with the first particle size is greater than that of the amorphous solid electrolyte particles with the second particle size.
[0026] On the other hand, an amorphous solid electrolyte is provided, which is prepared by the above preparation method.
[0027] On the other hand, a all-solid-state battery is provided, which includes the above amorphous solid electrolyte.
[0028] The amorphous solid electrolyte and its preparation method provided by this application have the following technical effects:
[0029] In this application, Li2CO3 and LiI are respectively weighed according to the molar ratio x:y to obtain the preparation raw materials; wherein, x + y = 1, 0 < x < 1, 0 < y < 1; the preparation raw materials and the ball-milling balls are placed in a ball-milling tank for ball-milling treatment to obtain the amorphous solid electrolyte xLi2CO3 - yLiI; wherein, the ball-milling time corresponding to the ball-milling treatment is 1 - 50 h, and the ball-milling speed is 200 - 500 rpm; the amorphous solid electrolyte xLi2CO3 - yLiI is formed by piling up multiple spherical amorphous solid electrolyte particles, and the particle size range of the amorphous solid electrolyte particles is 0.5 - 5 μm. This application uses the primary lithium salt product Li2CO3 as one of the raw materials, does not contain expensive Li2S, and does not contain S 2- ions that are unstable to water and oxygen, avoiding the problem of the instability of sulfide electrolyte materials to the lithium negative electrode; the preparation raw materials are inexpensive and the preparation method is simple, which is conducive to large-scale production; the simultaneous presence of the two anions CO3 2- , I - in xLi2CO3 - yLiI forms a structure with a higher configurational entropy, enhancing the Li+ The isotropic migration ability makes xLi2CO3-yLiI have a higher ionic conductivity; the prepared amorphous solid electrolyte xLi2CO3-yLiI has a non-flammable property, which is beneficial to improving the safety of the battery.
[0030] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions and advantages of the embodiments of this specification or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 It is a schematic flow chart of a method for preparing an amorphous solid electrolyte provided in an embodiment of this specification;
[0033] Figure 2 is a flow chart of a method for determining an amorphous solid electrolyte provided in an embodiment of this specification;
[0034] Figure 3 is a scanning electron microscope image of an amorphous solid electrolyte provided in an embodiment of this specification;
[0035] Figure 4 It is the XRD diffraction pattern of the 0.66Li2CO3-0.33LiI amorphous solid electrolyte provided in the examples of this specification;
[0036] Figure 5 is a conductivity change trend diagram of different x:y ratios in the xLi2CO3-yLiI amorphous solid electrolyte provided in the embodiments of this specification;
[0037] Figure 6 This is a schematic diagram of the structure of an all-solid-state battery using an xLi2CO3-yLiI amorphous solid electrolyte provided in an embodiment of this specification;
[0038] Figure 7 This is a schematic diagram of a Li / Li symmetric battery structure using an xLi2CO3-yLiI amorphous solid electrolyte provided in an embodiment of this specification. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of this specification to clearly and completely describe the technical solutions in the embodiments of this specification. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0040] The following describes a method for preparing an amorphous solid electrolyte of the present application, specifically as follows Figure 1 As shown, the method may include:
[0041] S1: Li2CO3 and LiI are weighed in a molar ratio of x:y to obtain a raw material; wherein x+y=1,0 <x<1,0<y<1。
[0042] In the present embodiment, primary lithium salt products Li2CO3 and LiI are used as raw materials for preparation, expensive Li2S is not used, and S that is unstable to water and oxygen is not contained. 2- Ions can be used to prepare materials that are stable to metallic lithium and stable at low potentials, and the raw materials are inexpensive, which is conducive to large-scale production.
[0043] In the present application example, CO3 2- ,I - The coexistence of these two anions forms a structure with high configurational entropy, which leads to local lattice distortion and Li + Site, Li + The change of migration channel and more uniform anion distribution change the Li + The binding energy landscape of Li + The isotropic mobility, the so-called "anion mixing effect", makes the conductivity of the final electrolyte higher than that of the amorphous state of each raw material alone.
[0044] S2: placing the prepared raw materials and ball milling balls in a ball milling jar for ball milling treatment to obtain the amorphous solid electrolyte xLi2CO3-yLiI; wherein the ball milling time corresponding to the ball milling treatment is 1-50h, and the ball milling speed is 200-500rpm; the amorphous solid electrolyte xLi2CO3-yLiI is formed by stacking a plurality of spherical amorphous solid electrolyte particles, and the particle size range of the amorphous solid electrolyte particles is 0.5-5μm.
[0045] Furthermore, if Figure 2 As shown, the preparation raw materials and ball milling balls are placed in a ball milling jar for ball milling to obtain the amorphous solid electrolyte xLi2CO3-yLiI, including:
[0046] S21: placing the raw material and the ball milling balls in the ball milling jar for ball milling to obtain a mixture of the ball milling balls and an initial product; the mass ratio of the raw material to the ball milling balls is 1:(1-50);
[0047] S22: performing an X-ray diffraction test on the initial product to obtain a test result of the initial product;
[0048] S23: If the test result of the initial product indicates that the initial product has no characteristic peak within the range of 2θ=20-30°, it is determined that the initial product is the amorphous solid electrolyte xLi2CO3-yLiI.
[0049] In an embodiment of the present application, the prepared raw materials and ball milling balls are placed in a ball mill for high-speed ball milling to induce an amorphization reaction to obtain an initial product; the mass ratio of the prepared raw materials to the ball milling balls can be in the range of 1: (1-50), preferably 1:20; the ball milling time can be in the range of 1-50h, preferably 30h; the ball milling speed can be in the range of 200-500rpm, preferably 400rpm.
[0050] In the embodiment of the present application, the initial product obtained by ball milling is subjected to XRD testing to obtain an XRD spectrum of the initial product. If the XRD spectrum shows that the initial product has no peak at 2θ=20-30° but only a peak package, the ball milling treatment can be stopped, and the product obtained by ball milling is the amorphous solid electrolyte xLi2CO3-yLiI.
[0051] In the embodiments of the present application, xLi2CO3-yLiI is completely amorphous.
[0052] The embodiment of the present application confirms the product obtained by ball milling through XRD testing, which can effectively obtain the process information of the amorphization reaction, ensure that the obtained product is amorphous, and improve the accuracy of the reaction.
[0053] Furthermore, the method further comprises:
[0054] If the test result of the initial product indicates that the initial product has the characteristic peak in the range of 2θ=20-30°, the ball milling treatment is continued until the product of the ball milling treatment has no characteristic peak in the range of 2θ=20-30°, and the product of the ball milling treatment is determined to be the amorphous solid electrolyte xLi2CO3-yLiI.
[0055] In the embodiment of the present application, if there are characteristic peaks in the XRD spectrum of the initial product, it indicates that the amorphization reaction has not been completely completed, and it is necessary to continue the ball milling treatment, and continue to perform XRD testing on the product obtained by the ball milling treatment until the product obtained by the ball milling treatment has no characteristic peaks in the range of 2θ=20-30°. Then, the ball milling treatment can be stopped, and the final product obtained by the ball milling treatment can be used as the amorphous solid electrolyte xLi2CO3-yLiI.
[0056] In the embodiment of the present application, the ball milling product is confirmed by XRD testing to complete the amorphization reaction, thereby ensuring that the final product is amorphous, thereby obtaining an amorphous solid electrolyte xLi2CO3-yLiI.
[0057] Further, if the test result of the initial product indicates that the initial product has no characteristic peak in the range of 2θ=20-30°, then after determining that the initial product is the amorphous solid electrolyte xLi2CO3-yLiI, the method comprises:
[0058] Transferring the mixture of the ball milling balls and the amorphous solid electrolyte from the ball milling jar to a screen;
[0059] The mixture of the ball milling balls and the amorphous solid electrolyte is separated by the sieve to obtain the amorphous solid electrolyte; the aperture of the sieve is smaller than the diameter of the ball milling balls.
[0060] In an embodiment of the present application, after determining that the product obtained by ball milling is an amorphous solid electrolyte xLi2CO3-yLiI, the mixture of the ball milling balls and the amorphous solid electrolyte is transferred from the ball milling tank, and then the mixture of the ball milling balls and the amorphous solid electrolyte is separated using a screen to remove the ball milling balls to obtain an amorphous solid electrolyte; wherein the aperture of the screen is smaller than the diameter of the ball milling balls, so that the ball milling balls remain on the screen, and the amorphous solid electrolyte sieved off the screen is collected to ensure that the ball milling balls and the amorphous solid electrolyte are completely separated.
[0061] The embodiment of the present application uses a screen to separate the mixture of ball milling balls and amorphous solid electrolyte, which can remove the ball milling balls and separate the ball milling balls from the amorphous solid electrolyte to obtain the amorphous solid electrolyte xLi2CO3-yLiI.
[0062] Furthermore, the ignition point of the amorphous solid electrolyte xLi2CO3-yLiI is greater than 1000°C.
[0063] In an embodiment of the present application, a combustion test was performed on the amorphous solid electrolyte xLi2CO3-yLiI. When 10g of xLi2CO3-yLiI was heated for 30s using the outer flame of a 1000°C alcohol blowtorch, the amorphous solid electrolyte xLi2CO3-yLiI was still non-flammable, indicating that it has stable physical properties and good safety, which is beneficial to improving the safety performance of the battery.
[0064] The amorphous solid electrolyte xLi2CO3-yLiI prepared in the embodiment of the present application has the physical property of being non-flammable, and can effectively improve the safety of all-solid-state batteries.
[0065] Furthermore, the ionic conductivity of the amorphous solid electrolyte xLi2CO3-yLiI is 4.9×10 -4 -8.8×10 -2 mS / cm.
[0066] In the embodiment of the present application, the conductivity of the amorphous solid electrolyte xLi2CO3-yLiI was tested, and the test results are shown in Table 1. As the amount of Li2CO3 increases, Figure 5 As shown in the figure, the conductivity of xLi2CO3-yLiI shows a trend of first decreasing, then increasing, and then decreasing. The ionic conductivity of xLi2CO3-yLiI is in the range of 4.9×10 -4 -8.8×10 -2 mS / cm. When x=0.66, y=0.33, the ionic conductivity of 0.66Li2CO3-0.33LiI is the highest, which is 8.8×10 -2 mS / cm.
[0067] The xLi2CO3-yLiI prepared in the embodiment of the present application has high ionic conductivity and can effectively improve the performance and efficiency of the battery.
[0068] Furthermore, the amorphous solid electrolyte particles include amorphous solid electrolyte particles of a first particle size and amorphous solid electrolyte particles of a second particle size; wherein the first particle size ranges from 2.1 to 5 μm, and the second particle size ranges from 0.2 to 2 μm.
[0069] In the examples of the present application, the scanning electron microscope image ( Figure 3 ) It can be seen that the amorphous solid electrolyte xLi2CO3-yLiI is formed by stacking a plurality of irregular spherical amorphous solid electrolyte particles, and the particle size range of the amorphous solid electrolyte particles is 0.5-5μm. Among them, the amorphous solid electrolyte particles include amorphous solid electrolyte particles of a first particle size and amorphous solid electrolyte particles of a second particle size, the first particle size ranges from 2.1-5μm, and the second particle size ranges from 0.2-2μm.
[0070] The amorphous solid electrolyte prepared in the embodiment of the present application is formed by stacking a plurality of amorphous solid electrolyte particles, which can provide sufficient channels for ion transport and improve the ionic conductivity of the amorphous solid electrolyte xLi2CO3-yLiI.
[0071] In the embodiment of the present application, for amorphous solid electrolyte particles with different particle sizes, the particle sizes can be adjusted by changing the ball milling time and the ball milling speed during the ball milling process, for example:
[0072] Placing the prepared raw materials and ball milling balls in a ball milling jar, and ball milling for 0.5-25 hours at 200-500 rpm to obtain an initial amorphous solid electrolyte; the initial amorphous solid electrolyte includes amorphous solid electrolyte particles of a first particle size;
[0073] The initial amorphous solid electrolyte is ball-milled for 0.5-25 hours at 200-500 rpm to obtain a target amorphous solid electrolyte; the target amorphous solid electrolyte includes amorphous solid electrolyte particles of the first particle size and amorphous solid electrolyte particles of the second particle size.
[0074] Furthermore, the above method may include:
[0075] Placing the prepared raw materials and ball milling balls in a ball milling jar, and ball milling for 0.5 h at 200 rpm to obtain an initial amorphous solid electrolyte; the initial amorphous solid electrolyte includes amorphous solid electrolyte particles of a first particle size;
[0076] The initial amorphous solid electrolyte is ball-milled for 0.5 h at 300 rpm to obtain a target amorphous solid electrolyte; the target amorphous solid electrolyte includes amorphous solid electrolyte particles of the first particle size and amorphous solid electrolyte particles of the second particle size.
[0077] In an embodiment of the present application, the particle size of the amorphous solid electrolyte particles can be further divided into more particle size ranges. In addition to the above-mentioned method, more ball milling treatments can be performed, and more electrolyte particles with different particle size ranges can be obtained. Different ball milling speeds and ball milling times can be used in the multiple ball milling processes to achieve a more ideal distribution of amorphous solid electrolyte particles, thereby obtaining an amorphous solid electrolyte material with higher electrical conductivity. In addition, by setting appropriate ball milling parameters, the final amorphous solid electrolyte can also be obtained at one time to simplify the preparation method and improve the preparation efficiency.
[0078] Embodiments of the present application can obtain amorphous solid electrolyte particles with different particle size distributions by changing the ball milling treatment parameters (such as ball milling time, ball milling speed, etc.) during ball milling treatment, so as to optimize the particle distribution inside the amorphous solid electrolyte, provide sufficient channels for ion transport, and improve the ionic conductivity of the amorphous solid electrolyte.
[0079] Further, the number of amorphous solid electrolyte particles with the first particle size is greater than that of the amorphous solid electrolyte particles with the second particle size.
[0080] In the embodiments of the present application, the number of amorphous solid electrolyte particles with the first particle size is greater than that of the amorphous solid electrolyte particles with the second particle size, which indicates that the particle sizes of the prepared amorphous solid electrolyte particles are relatively uniform. Most of the amorphous solid electrolyte particles have particle sizes in the range of 2.1 - 5 μm, which is beneficial to obtaining an amorphous solid electrolyte xLi2CO3 - yLiI with a relatively uniform internal particle size, providing sufficient channels for ion transport, promoting ion transport, and improving the ionic conductivity of the amorphous solid electrolyte xLi2CO3 - yLiI.
[0081] The particle distribution of the amorphous solid electrolyte particles in the embodiments of the present application can effectively improve the ionic conductivity of the amorphous solid electrolyte xLi2CO3 - yLiI, and enhance the performance and efficiency of the battery.
[0082] In the embodiments of the present application, two raw materials Li2CO3 and LiI are weighed according to the molar ratio x:y, where x + y = 1, 0 < x < 1, and 0 < y < 1; then the two raw materials and the ball milling balls are placed in a ball milling jar according to a certain mass ratio for high - speed ball milling, and finally the amorphous solid electrolyte xLi2CO3 - yLiI is obtained.
[0083] The preparation method provided by the embodiments of the present application can prepare an amorphous solid electrolyte xLi2CO3 - yLiI, where x + y = 1, 0 < x < 1, and 0 < y < 1. This amorphous solid electrolyte xLi2CO3 - yLiI is a brand - new solid electrolyte component, does not contain expensive Li2S, only uses the primary lithium salt product Li2CO3, and does not contain S 2- ions that are unstable to water and oxygen. The material is stable to metallic lithium and stable at low potentials; the raw materials are inexpensive and the preparation method is simple, which is beneficial to large - scale production; in addition, the anions in xLi2CO3 - yLiI are CO3 2- and I - , and the simultaneous presence of the two anions forms a structure with a relatively high configurational entropy. The high configurational entropy leads to local lattice distortion and changes in the Li + sites and Li + migration channels. The more uniform anion distribution changes the binding energy trend of Li + and improves the Li+ The isotropic migration ability makes xLi2CO3-yLiI have a higher ionic conductivity; and the non-flammable property of xLi2CO3-yLiI can effectively improve the safety of the battery.
[0084] An embodiment of the present application also provides an all-solid-state battery, which includes a composite positive electrode layer containing a positive electrode active material and an electrolyte, a composite negative electrode layer containing a negative electrode active material and an electrolyte, and an electrolyte layer serving as an isolation layer between the positive and negative electrodes.
[0085] In an embodiment of the present application, at least one of the composite positive electrode layer, the composite negative electrode layer and the isolation layer contains the above-mentioned amorphous solid electrolyte xLi2CO3-yLiI, and xLi2CO3-yLiI is preferably selected as the electrolyte in the composite negative electrode layer or on the isolation layer side close to the negative electrode layer.
[0086] In the embodiment of the present application, the positive electrode active material may include: rock salt layer type active material, such as LiCoO2, LiMnO2, LiNiO2, LiVO2 or Li 1+x Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O2; spinel active materials, such as LiMn2O4 or Li(Ni 0.5 Mn 1.5 )O4; inverse spinel type active materials, such as LiNiVO4 or LiCoVO4; olivine type active materials, such as LiFePO4, LiMnPO4, LiCoPO4 or LiNiPO4; silicon-containing active materials, such as Li2FeSiO4 or Li2MnSiO; rock salt layer type active materials in which a portion of transition metals are replaced by heterogeneous metals, such as LiNi 0.8 Co (0.2-x) Al x O2 (0<x<0.2); spinel-type active materials in which a portion of transition metals are replaced by heterogeneous metals, such as Li 1+x Mn 2-x-y M y O4 (wherein M includes at least one of Al, Mg, Co, Fe, Ni, and Zn, and 0<x+y<2); and lithium titanate, such as Li4Ti5O 12 ; and sulfide positive electrode active materials, including: copper sulfide, iron sulfide, cobalt sulfide, nickel sulfide, etc.
[0087] In the embodiment of the present application, the negative electrode active material may include: a metal material, a carbon material, an oxide, a nitride, a tin compound or a silicon compound, etc. The metal material may be a single metal material, or may be an alloy. Examples of metal materials are lithium metal or lithium alloys. Examples of carbon materials are natural graphite, coke, graphitizable carbon, carbon fiber, spherical carbon, artificial graphite or amorphous carbon, etc. From the viewpoint of capacity density, suitable examples of negative electrode active materials are silicon, tin, silicon compounds or tin compounds.
[0088] In the embodiment of the present application, in addition to the xLi2CO3-yLiI electrolyte, the solid electrolyte in the composite positive electrode layer, the composite negative electrode layer, and the electrolyte layer may include Li3YCl6, Li3InCl6, Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers, and Z is one of Ge, Zn and Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (where x and y are positive numbers, and M is one of P, Si, Ge, B, Al, Ga, and In), Li 10 GeP2S 12 wait.
[0089] Embodiment 1:
[0090] This embodiment provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.66, y=0.33, and the specific preparation method includes:
[0091] Weigh 4.877 g of Li2CO3 and 4.417 g of LiI in a molar ratio of 0.66:0.33 to obtain 9.294 g of raw material;
[0092] 9.294 g of the raw material and 186 g of zirconium dioxide ball milling balls were placed in a 2 L zirconium dioxide ball milling jar and milled at 400 rpm for 30 h to obtain an amorphous solid electrolyte 0.66Li2CO3-0.33LiI. Its XRD spectrum is shown in Figure 4 shown.
[0093] Embodiment 2:
[0094] This embodiment provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.1, y=0.9, and the specific preparation method includes:
[0095] Weigh 0.739 g of Li2CO3 and 12.046 g of LiI in a molar ratio of 0.1:0.9 to obtain 12.785 g of raw material;
[0096] 12.785 g of the raw material and 255.7 g of zirconium dioxide ball milling balls were placed in a 2-L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 400 rpm for 30 h to obtain an amorphous solid electrolyte 0.1Li2CO3-0.9LiI.
[0097] Embodiment 3:
[0098] This embodiment provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.2, y=0.8, and the specific preparation method includes:
[0099] 1.478 g of Li2CO3 and 10.708 g of LiI were weighed in a molar ratio of 0.2:0.8 to obtain 12.186 g of raw material;
[0100] 12.186 g of the raw material and 243.7 g of zirconium dioxide ball milling balls were placed in a 2-L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 400 rpm for 30 h to obtain an amorphous solid electrolyte 0.2Li2CO3-0.8LiI.
[0101] Embodiment 4:
[0102] This embodiment provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.3, y=0.7, and the specific preparation method includes:
[0103] Weigh 2.217 g of Li2CO3 and 9.369 g of LiI in a molar ratio of 0.3:0.7 to obtain 11.586 g of raw material;
[0104] 11.586 g of the raw material and 231.7 g of zirconium dioxide ball milling balls were placed in a 2-L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 400 rpm for 30 h to obtain an amorphous solid electrolyte 0.3Li2CO3-0.7LiI.
[0105] Embodiment 5:
[0106] This embodiment provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.4, y=0.6, and the specific preparation method includes:
[0107] Weigh 2.956 g of Li2CO3 and 8.031 g of LiI in a molar ratio of 0.4:0.6 to obtain 10.987 g of raw material;
[0108] 10.987 g of the raw material and 219.7 g of zirconium dioxide ball milling balls were placed in a 2-L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 400 rpm for 30 h to obtain an amorphous solid electrolyte 0.4Li2CO3-0.6LiI.
[0109] Embodiment 6:
[0110] This embodiment provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.5, y=0.5, and the specific preparation method includes:
[0111] Weigh 3.695 g of Li2CO3 and 6.692 g of LiI at a molar ratio of 0.5:0.5 to obtain 10.387 g of raw material;
[0112] 10.387 g of the raw material and 207.7 g of zirconium dioxide ball milling balls were placed in a 2-L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 400 rpm for 30 h to obtain an amorphous solid electrolyte 0.5Li2CO3-0.5LiI.
[0113] Embodiment 7:
[0114] This embodiment provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.6, y=0.4, and the specific preparation method includes:
[0115] Weigh 4.433 g of Li2CO3 and 5.354 g of LiI in a molar ratio of 0.6:0.4 to obtain 9.787 g of raw material;
[0116] 9.787 g of the raw material and 195.7 g of zirconium dioxide ball milling balls were placed in a 2-L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 400 rpm for 30 h to obtain an amorphous solid electrolyte 0.6Li2CO3-0.4LiI.
[0117] Embodiment 8:
[0118] This embodiment provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.7, y=0.3, and the specific preparation method includes:
[0119] Weigh 5.172 g of Li2CO3 and 4.015 g of LiI in a molar ratio of 0.7:0.3 to obtain 9.187 g of raw material;
[0120] 9.187 g of the raw material and 183.7 g of zirconium dioxide ball milling balls were placed in a 2-L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 400 rpm for 30 h to obtain an amorphous solid electrolyte 0.7Li2CO3-0.3LiI.
[0121] Embodiment 9:
[0122] This embodiment provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.8, y=0.2, and the specific preparation method includes:
[0123] Weigh 5.911 g of Li2CO3 and 2.677 g of LiI in a molar ratio of 0.8:0.2 to obtain 8.588 g of raw material;
[0124] 8.588 g of the raw material and 171.8 g of zirconium dioxide ball milling balls were placed in a 2-L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 400 rpm for 30 h to obtain an amorphous solid electrolyte 0.8Li2CO3-0.2LiI.
[0125] Embodiment 10:
[0126] This embodiment provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.9, y=0.1, and the specific preparation method includes:
[0127] Weigh 6.65 g of Li2CO3 and 1.338 g of LiI in a molar ratio of 0.9:0.1 to obtain 7.988 g of raw materials;
[0128] 7.988 g of the raw material and 159.8 g of zirconium dioxide ball milling balls were placed in a 2-L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 400 rpm for 30 h to obtain an amorphous solid electrolyte 0.9Li2CO3-0.1LiI.
[0129] Embodiment 11:
[0130] This embodiment provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.66, y=0.33, and the specific preparation method includes:
[0131] Weigh 4.877 g of Li2CO3 and 4.417 g of LiI in a molar ratio of 0.66:0.33 to obtain 9.294 g of raw material;
[0132] 9.294 g of the raw material and 9.29 g of zirconium dioxide ball milling balls were placed in a 2-L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 400 rpm for 30 h to obtain an amorphous solid electrolyte 0.66Li2CO3-0.33LiI.
[0133] Embodiment 12:
[0134] This embodiment provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.66, y=0.33, and the specific preparation method includes:
[0135] Weigh 4.877 g of Li2CO3 and 4.417 g of LiI in a molar ratio of 0.66:0.33 to obtain 9.294 g of raw materials;
[0136] 9.294 g of the raw material and 465 g of zirconium dioxide ball milling balls were placed in a 2 L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 400 rpm for 30 h to obtain an amorphous solid electrolyte 0.66Li2CO3-0.33LiI.
[0137] Embodiment 13:
[0138] This embodiment provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.66, y=0.33, and the specific preparation method includes:
[0139] Weigh 4.877 g of Li2CO3 and 4.417 g of LiI in a molar ratio of 0.66:0.33 to obtain 9.294 g of raw materials;
[0140] 9.294 g of the raw material and 186 g of zirconium dioxide ball milling balls were placed in a 2 L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 400 rpm for 1 h to obtain an amorphous solid electrolyte 0.66Li2CO3-0.33LiI.
[0141] Embodiment 14:
[0142] This embodiment provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.66, y=0.33, and the specific preparation method includes:
[0143] Weigh 4.877 g of Li2CO3 and 4.417 g of LiI in a molar ratio of 0.66:0.33 to obtain 9.294 g of raw materials;
[0144] 9.294 g of the raw material and 186 g of zirconium dioxide ball milling balls were placed in a 2 L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 400 rpm for 50 h to obtain an amorphous solid electrolyte 0.66Li2CO3-0.33LiI.
[0145] Embodiment 15:
[0146] This embodiment provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.66, y=0.33, and the specific preparation method includes:
[0147] Weigh 4.877 g of Li2CO3 and 4.417 g of LiI in a molar ratio of 0.66:0.33 to obtain 9.294 g of raw materials;
[0148] 9.294 g of the raw material and 186 g of zirconium dioxide ball milling balls were placed in a 2 L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 200 rpm for 30 h to obtain an amorphous solid electrolyte 0.66Li2CO3-0.33LiI.
[0149] Embodiment 16:
[0150] This embodiment provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.66, y=0.33, and the specific preparation method includes:
[0151] Weigh 4.877 g of Li2CO3 and 4.417 g of LiI in a molar ratio of 0.66:0.33 to obtain 9.294 g of raw materials;
[0152] 9.294 g of the raw material and 186 g of zirconium dioxide ball milling balls were placed in a 2-L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 500 rpm for 30 h to obtain an amorphous solid electrolyte 0.66Li2CO3-0.33LiI.
[0153] Comparative Example 1:
[0154] This comparative example provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0, y=1, and the specific preparation method includes:
[0155] Weigh 13.385 g of LiI to obtain 133.385 g of preparation raw material;
[0156] 13.385 g of the raw material and 267.7 g of zirconium dioxide ball milling balls were placed in a 2 L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 400 rpm for 30 h to obtain 0Li2CO3-1LiI.
[0157] Comparative Example 2:
[0158] This comparative example provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=1, y=0, and the specific preparation method includes:
[0159] Weigh 7.389 g of Li2CO3 to obtain 7.389 g of preparation raw material;
[0160] 7.389 g of the raw material and 147.8 g of zirconium dioxide ball milling balls were placed in a 2 L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 400 rpm for 30 h to obtain 1Li2CO3-0LiI.
[0161] Comparative Example 3:
[0162] This comparative example provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.66, y=0.33, and the specific preparation method includes:
[0163] Weigh 4.877 g of Li2CO3 and 4.417 g of LiI in a molar ratio of 0.66:0.33 to obtain 9.294 g of raw materials;
[0164] 9.294 g of the raw material and 557 g of zirconium dioxide ball milling balls were placed in a 2-L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 400 rpm for 30 h to obtain an amorphous solid electrolyte 0.66Li2CO3-0.33LiI.
[0165] Comparative Example 4:
[0166] This embodiment provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.66, y=0.33, and the specific preparation method includes:
[0167] Weigh 4.877 g of Li2CO3 and 4.417 g of LiI in a molar ratio of 0.66:0.33 to obtain 9.294 g of raw materials;
[0168] 9.294 g of the raw material and 186 g of zirconium dioxide ball milling balls were placed in a 2 L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 400 rpm for 0.5 h to obtain an amorphous solid electrolyte 0.66Li2CO3-0.33LiI.
[0169] Comparative Example 5:
[0170] This embodiment provides an amorphous solid electrolyte xLi2CO3-yLiI and a preparation method thereof, wherein x=0.66, y=0.33, and the specific preparation method includes:
[0171] Weigh 4.877 g of Li2CO3 and 4.417 g of LiI in a molar ratio of 0.66:0.33 to obtain 9.294 g of raw materials;
[0172] 9.294 g of the raw material and 186 g of zirconium dioxide ball milling balls were placed in a 2-L zirconium dioxide ball milling jar and subjected to high-speed ball milling at 100 rpm for 30 h to obtain an amorphous solid electrolyte 0.66Li2CO3-0.33LiI.
[0173] In the embodiments of the present application, the difference between Example 2 and Example 1 is that x=0.1, y=0.9, and the other conditions are the same as those of Example 1; the difference between Example 3 and Example 1 is that x=0.2, y=0.8, and the other conditions are the same as those of Example 1; the difference between Example 4 and Example 1 is that x=0.3, y=0.7, and the other conditions are the same as those of Example 1; the difference between Example 5 and Example 1 is that x=0.4, y=0.6, and the other conditions are the same as those of Example 1; the difference between Example 6 and Example 1 is that x=0.5, y=0.5, and the other conditions are the same as those of Example 1. The conditions are the same as those in Example 1; the difference between Example 7 and Example 1 is that x=0.6, y=0.4, and the other conditions are the same as those in Example 1; the difference between Example 8 and Example 1 is that x=0.7, y=0.3, and the other conditions are the same as those in Example 1; the difference between Example 9 and Example 1 is that x=0.8, y=0.2, and the other conditions are the same as those in Example 1; the difference between Example 10 and Example 1 is that x=0.9, y=0.1, and the other conditions are the same as those in Example 1; the difference between Example 11 and Example 1 is that the weight of the ball mill is 9.29 g , other conditions are the same as those in Example 1; the difference between Example 12 and Example 1 is that the weight of the ball milling balls is 465 g, and other conditions are the same as those in Example 1; the difference between Example 13 and Example 1 is that the ball milling time is 1 h, and other conditions are the same as those in Example 1; the difference between Example 14 and Example 1 is that the ball milling time is 50 h, and other conditions are the same as those in Example 1; the difference between Example 15 and Example 1 is that the ball milling speed is 200 rpm, and other conditions are the same as those in Example 1; the difference between Example 16 and Example 1 is that the ball milling speed is 500 rpm, and the The other conditions are the same as those in Example 1; the difference between Comparative Example 1 and Example 1 is that x=0, y=1, and the other conditions are the same as those in Example 1; the difference between Comparative Example 2 and Example 1 is that x=1, y=0, and the other conditions are the same as those in Example 1; the difference between Comparative Example 3 and Example 1 is that the weight of the ball milling balls is 557 g, and the other conditions are the same as those in Example 1; the difference between Comparative Example 4 and Example 1 is that the ball milling time is 0.5 h, and the other conditions are the same as those in Example 1; the difference between Comparative Example 5 and Example 1 is that the ball milling speed is 100 rpm, and the other conditions are the same as those in Example 1.
[0174] In the examples of the present application, the amorphous solid electrolytes prepared in the above-mentioned examples and comparative examples were subjected to XRD test, conductivity test, all-solid-state battery test, Li / Li symmetric battery impedance change test and combustion test.
[0175] In the examples of the present application, the XRD test method is as follows: in an argon atmosphere, an X-ray diffraction device is used to measure the X-ray diffraction patterns of the solid electrolyte materials of some examples and comparative examples, using Cu-Kα rays as the X-ray source.
[0176] In the embodiments of the present application, the test method of the conductivity test is as follows: in an argon atmosphere, the powder of the solid electrolyte material of some embodiments and the comparative example is filled inside a pressurized mold. Inside the pressurized mold, a pressure of 500MPa is applied to the powder of the solid electrolyte material using upper and lower punches. Keeping the state of applying pressure unchanged, the upper part of the punch and the lower part of the punch are respectively connected to a constant potential instrument equipped with a frequency response analyzer, and the ionic conductivity of the solid electrolyte material is measured by the electrochemical impedance method. The real value of the impedance at the measuring point where the absolute value of the phase of the complex impedance is the smallest is regarded as the resistance value of the solid electrolyte material to ionic conduction.
[0177] In the embodiment of the present application, the test method of the all-solid-state battery test is: Li6PS5Cl solid electrolyte material and positive electrode active material, i.e. LiCoO2, are mixed in an agate mortar in a mass ratio of 30:70. These materials are mixed to obtain a positive electrode mixture. In an insulating cylinder, Li6PS5Cl solid electrolyte material (60 mg) and xLi2CO3-yLiI (6 mg) are stacked in sequence to obtain a laminate. A pressure of 160 MPa is applied to the laminate to form a solid electrolyte layer. Then, on the Li6PS5Cl solid electrolyte layer, a positive electrode mixture (5 mg) is stacked to obtain a laminate. A pressure of 360 MPa is applied to the laminate to form a positive electrode. Then, a metal Li foil (thickness of 300 μm) is stacked on the solid electrolyte layer formed by xLi2CO3-yLiI to obtain a laminate. A pressure of 5 MPa is applied to the laminate to form a negative electrode. A current collector made of stainless steel is placed on the positive electrode and the negative electrode, and a current collector lead is installed on the current collector. Finally, an insulating hoop is used to isolate the inside of the insulating tube from the external atmosphere, and the inside of the tube is sealed to obtain an all-solid-state battery. Figure 6 The battery was tested for 0.1-1C electrochemical performance in the voltage range of 2.5-4.2V.
[0178] In an embodiment of the present application, the test method of the impedance change test of the Li / Li symmetric battery is as follows: in an argon atmosphere, in an insulating cylinder, xLi2CO3-yLiI (24 mg) is stacked, and a pressure of 360 MPa is applied to the stack to form a solid electrolyte layer. Next, metal Li foil (300 μm thick) is stacked on both sides of the solid electrolyte layer formed by xLi2CO3-yLiI to obtain a stack. A pressure of 5 MPa is applied to the stack to form a symmetrical negative electrode. A current collector formed of stainless steel is arranged on the negative electrode, and a current collecting lead is installed on the current collector. Finally, an insulating hoop is used to isolate the inside of the insulating cylinder from the external atmosphere, and the inside of the cylinder is sealed to obtain a Li / Li symmetric battery, such as Figure 7 The battery was placed in a 60°C oven, and electrochemical impedance tests were performed on the first day, Day 1, and the 100th day, Day 100.
[0179] In the embodiment of the present application, the test method of the combustion test is: in an air atmosphere, use the outer flame of a 1000°C alcohol blowtorch to heat 10g of xLi2CO3-yLiI for 30s, and observe its combustion conditions.
[0180] Table 1. Physical property test results of different samples and all-solid-state battery cycle performance
[0181]
[0182] In the examples of the present application, the test data of the electrolytes obtained in the above examples and comparative examples are shown in Table 1. From the test data of Examples 1-10 and Comparative Examples 1-2, it can be seen that with the increase of Li2CO3, the conductivity shows a trend of first decreasing, then increasing, and then decreasing: from 2.9×10 -3 mS / cm is reduced to 2.0×10 of 0.1Li2CO3-0.9LiI - 3 mS / cm, and then increased to 8.8×10 -2 mS / cm, and then reduced to 4.9×10 -4 mS / cm, and finally decreased to 2.4×10 -6 mS / cm. The decrease in conductivity after adding 10% Li2CO3 may be due to the lower ionic conductivity, and the so-called "anion mixing effect" has not occurred; after adding 40% Li2CO3, CO3 2- ,I - The coexistence of the two anions forms a structure with high configurational entropy, which leads to local lattice distortion and Li +Site, Li + The change of the migration channel and the more uniform anion distribution change the + binding energy landscape of Li, enhancing the + isotropic migration ability of Li, that is, this makes the conductivity of the electrolyte higher than that of the amorphous state of each raw material alone. The highest point is at 8.8×10 -2 mS / cm for 0.66Li2CO3 - 0.33LiI. The rate performance of the battery also corroborates the above analysis and conclusion.
[0183] In the embodiments of the present application, it can be obtained from Example 1, Examples 11 - 16 and Comparative Examples 3 - 5 that in the process of preparing 0.66Li2CO3 - 0.33LiI, the weight ratio of the raw material to the ball - milling ball can be in the range of 1:1 to 1:50, preferably 1:20; the ball - milling time can be in the range of 1 - 50 h, preferably 30 h; the ball - milling speed can be in the range of 200 - 500 rpm, preferably 400 rpm.
[0184] In the embodiments of the present application, it can be obtained from the Li / Li symmetric battery test in Table 1 that for 0.66Li2CO3 - 0.33LiI, there is no obvious change in the electrochemical impedance during the static placement of metallic lithium in an oven environment at 60 °C for 100 days, that is, the 0.66Li2CO3 - 0.33LiI material is stable to metallic lithium; and the combustion test also shows that 0.66Li2CO3 - 0.33LiI is non - combustible under the heating of the outer flame of an alcohol blowtorch at 1000 °C, which is beneficial to improving the battery safety.
[0185] As can be seen from the above - mentioned embodiments provided by the present application, in the present application, Li2CO3 and LiI are weighed according to the molar ratio x:y to obtain the preparation raw materials; wherein, x + y = 1, 0 < x < 1, 0 < y < 1; the preparation raw materials and the ball - milling balls are placed in a ball - milling tank for ball - milling treatment to obtain an amorphous solid electrolyte xLi2CO3 - yLiI; wherein, the ball - milling time corresponding to the ball - milling treatment is 1 - 50 h, and the ball - milling speed is 200 - 500 rpm; the amorphous solid electrolyte xLi2CO3 - yLiI is composed of a plurality of spherical - like amorphous solid electrolyte particles stacked together, and the particle size range of the amorphous solid electrolyte particles is 0.5 - 5 μm. The amorphous solid electrolyte xLi2CO3 - yLiI prepared in the present application, wherein x + y = 1, 0 < x < 1, 0 < y < 1, is a brand - new solid electrolyte component, does not contain expensive Li2S, only uses the primary lithium salt product Li2CO3, does not contain S 2- ions that are unstable to water and oxygen, the material is stable to metallic lithium and stable at low potentials; the raw materials are inexpensive and the preparation method is simple, which is conducive to large - scale production; the anion in xLi2CO3 - yLiI is CO32- ,I - The simultaneous presence of two anions forms a structure with higher configurational entropy, which makes xLi2CO3-yLiI have higher ionic conductivity and can effectively improve the performance of the battery. In addition, xLi2CO3-yLiI has the property of being non-flammable, which can effectively improve the safety performance of the battery.
[0186] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing an amorphous solid electrolyte, characterized in that: The method comprises: Li2CO3 and LiI are weighed in a molar ratio of x:y to obtain a raw material; wherein x+y=1,0 <x<1,0<y<1; The prepared raw materials and ball milling balls are placed in a ball milling jar for ball milling to obtain the amorphous solid electrolyte xLi2CO3-yLiI; wherein the ball milling time corresponding to the ball milling treatment is 1-50h, and the ball milling speed is 200-500rpm; the amorphous solid electrolyte xLi2CO3-yLiI is formed by stacking a plurality of spherical amorphous solid electrolyte particles, and the particle size range of the amorphous solid electrolyte particles is 0.5-5μm.
2. The method according to claim 1, characterized in that The preparation raw materials and ball milling balls are placed in a ball milling jar for ball milling to obtain the amorphous solid electrolyte xLi2CO3-yLiI, comprising: Placing the raw material and the ball milling balls in the ball milling jar for ball milling to obtain a mixture of the ball milling balls and the initial product; the mass ratio of the raw material to the ball milling balls is 1:(1-50); Performing an X-ray diffraction test on the initial product to obtain a test result of the initial product; If the test result of the initial product indicates that the initial product has no characteristic peak within the range of 2θ=20-30°, it is determined that the initial product is the amorphous solid electrolyte xLi2CO3-yLiI.
3. The method according to claim 2, characterized in that The method further comprises: If the test result of the initial product indicates that the initial product has the characteristic peak in the range of 2θ=20-30°, the ball milling treatment is continued until the product of the ball milling treatment has no characteristic peak in the range of 2θ=20-30°, and the product of the ball milling treatment is determined to be the amorphous solid electrolyte xLi2CO3-yLiI.
4. The method according to claim 2, characterized in that: If the test result of the initial product indicates that the initial product has no characteristic peak in the range of 2θ=20-30°, then after determining that the initial product is the amorphous solid electrolyte xLi2CO3-yLiI, the method comprises: Transferring the mixture of the ball milling balls and the amorphous solid electrolyte from the ball milling jar to a screen; The mixture of the ball milling balls and the amorphous solid electrolyte is separated by the sieve to obtain the amorphous solid electrolyte; the aperture of the sieve is smaller than the diameter of the ball milling balls.
5. The method according to claim 1, characterized in that The ignition point of the amorphous solid electrolyte xLi2CO3-yLiI is greater than 1000°C.
6. The method according to claim 1, characterized in that The ionic conductivity of the amorphous solid electrolyte xLi2CO3-yLiI is 4.9×10 -4 -8.8×10 -2 mS / cm.
7. The method according to claim 1, characterized in that The amorphous solid electrolyte particles include amorphous solid electrolyte particles of a first particle size and amorphous solid electrolyte particles of a second particle size; wherein the first particle size ranges from 2.1 to 5 μm, and the second particle size ranges from 0.2 to 2 μm.
8. The method according to claim 7, characterized in that The number of amorphous solid electrolyte particles having the first particle size is greater than the number of amorphous solid electrolyte particles having the second particle size.
9. An amorphous solid electrolyte, characterized in that: The amorphous solid electrolyte is prepared by the preparation method according to any one of claims 1 to 8.
10. An all-solid-state battery, characterized in that: The all-solid-state battery comprises the amorphous solid electrolyte as claimed in claim 9.
